Self-Awareness of Sleep Apnea Symptoms Among Middle-Aged and Elderly People in Taiwan - Hsueh, Meng-Lun; Jong, Din (Frontiers in Psychiatry, 2022)
In recent years, the proportion of middle-aged and elderly people in Taiwan has gradually increased and has already surpassed that of advanced countries such as Europe, the United States and Japan, therefore, the health of middle-aged and elderly people is a topic that needs attention. This is because physical deterioration or illness can lead to a decline in quality of life and create a medical burden on the individual and society. This study investigated the common symptoms of sleep apnea in middle-aged and elderly people (over 40 years old), and developed a self-test subjective perception model, using "daytime sleepiness" and "sleep quality" as influencing factors, and "attention" as mediating variables to verify the effect with sleep apnea symptoms. An online electronic questionnaire was conducted and distributed through social media and groups of friends in Taiwan. A total of 450 questionnaires were collected and analyzed in three stages: Descriptive Analysis, Measurement Model Validation, and Structural Equation Model. The research processes of the study showed that the sample fitted the normal distribution and the measurement model conformed with convergent reliability and discriminant validity. The research results were found that "sleep quality" had a significant negative effect on sleep apnea symptoms. "Daytime sleepiness" had a positive effect on sleep apnea symptoms. "Daytime sleepiness" had a negative effect on sleep apnea symptoms through the "attention" mediator. Finally, through the questionnaire, we hope to make the middle-aged people aware of themselves, so that they can seek early medical treatment if there are signs and symptoms of sleep apnea symptoms.